(untitled) (Czech Journal of International Relations, 2002)
This essay is an analysis of the development of Islamic fundamentalism in one of the most significant countries of the Islamic world. Like many other regimes, Egypt struggled in the 90’s with armed Islamic opposition, which had world-wide connections to international terrorism by radical Islamic groups. The challenge is to identify the reasons behind the origin of these Islamic movements, as well as to identify their central characteristics and the tactics they use. As well as do this, the author tries to map the most important contacts of Egyptian movements abroad. The first part of the contribution describes the evolution of Egypt in the 20th century up to the assassination of president Sadat in 1981. The rise of Islamist organizations, the attempts to quell them during Nasser’s presidency and Sadat’s subsequent failure to conciliate Islamist opponents are events that are key to understanding Islamism in Egypt. Although the contribution is country-specific, it can be seen also as a more general model of Islamic fundamentalism, which explains one of the most urgent problems of today’s world. The main part of the article looks at the reaction of the Egyptian regime to violent Islamist opposition in the 80’s and 90’s and how the regime tried to solve this problem. The author attempts to outline the profiles of the main radical groups and evaluate the reaction of the regime. The regime must face Islamism not only on the ’battlefield’, but the solution of social problems and attitudes to culture are essential too. Resolving these problems in Egypt must involve every important sphere of national life if the regime wants stability. However, if the Egyptian difficulties are dealt with successfully, it could provide the formula for war-weary states in crisis areas across the Islamic world.